Evaluation of female pelvic mass - correlation of clinical and histopathological findings in female patients attending at Birat Medical College and Teaching Hospital, Morang, Nepal - Mishra, Seema Kumari; Pradhan, Roshan; Pokharel, Hanoon P (Birat Journal of Health Sciences, 2020)
Introduction: The female pelvis is a quite complex anatomical region consisting of uro-genital system as its main part and other structures like blood vessels, gastrointestinal tracts, lymphatics, nerves and a part of musculoskeletal system. Thus, the differential diagnosis of pelvic masses may be of gynecological or non gynecological origin. Gynecological pelvic masses are uterine, ovarian or adnexal masses which may be benign or malignant. Objective: The objective of this study was to evaluate the type of various gynecological pelvic masses and to correlate the preoperative diagnosis with histopathological diagnosis. Methodology: This was a hospital based cross sectional study conducted on 107 patients from September 2018 to September 2019 at Birat Medical College and Teaching Hospital (BMCTH) with presenting complian of lump in the abdomen. These patients underwent clinical examination, routine and specific investigations along with ultrasonographic evaluation and tumour markers to reach a preoperative clinical diagnosis. Patients were admitted and preanesthetic consultation was done. Patients were taken for therapeutic or diagnostic laparoscopy or exploratory laparotomy and diagnosis were confirmed with histopathological diagnosis. Results: Total 107 patients were enrolled in the study with age ranging from 21 to ≥70 years and among them majority (42.1%) were in the age group of 41-50 years. The most common presenting complain of patients were lower abdominopelvic pain (58.87%). The most common clinical diagnosis was leiomyoma in 39.25% patients followed by adenomyosis in 24.29% patients. The most common histopathological diagnosis was fibroid uterus seen in 42.05% patients. There were 2 (1.86%) patients of ovarian malignancies and 1 (0.93%) patient of uterine malignancy.